THE FOLKTALES OF LOMBOK: FAIRY TALES OF CUPAK GERANTANG, SANDUBAYA AND LALA SERUNI, AND CILINAYAA NARATIVE STRUCTURAL REVIEW OF VLADIMIR PROPP - Khaeriati Khaeriati (Educatio, 2009)
This research aims to applicated the Vladimir Proppâ€™s narative structures theory and the social philology, in order to find the sum of functions in the Cupak Gerantang, Sandubaya and Lala Seruni, and Cilinayaâ€™s tales text; to find out the social function in those three of tales obove. The research methods related to theory used was qualitative methods, structural, social philology. Collecting data by interview and documentation. Vladimir Propps narative structural methods consist of: function order, function groupig into action circle. Social philology methods used to ascertain the social function in those three tales to get the socual value in them. The results of the study as follows; The three stories have different functions, orderly and systematically. The story of Cupak Gerantang has 18 function, Sandubaya and Lala Seruni has 9 functions, and Cilinaya has 14 functions. The action environment of the three stories are also different, in the story of Cupak Gerantang there is 6 action environments, Sandubaya and lala Seruni consist of 4 action environments and Cilinaya consist of 3 action environments. Social functions of the three stories comprise: entertain function, educational function, adversary function, hidden intentional function, religious function and solidarity function. Social values of the three stories consist of etiquette and politeness values, critiques for the kings values, sacrification values togetherness values and working together, bravery attitudes, noble quality and sportive values. Key Words: folktales story of Lombok, narrative structure, social function, social value